Two pairs of back-to-back α-helices of Kingella kingae RtxA toxin are crucial for the formation of a membrane pore - Ruzickova, Eliska; Lichvarova, Michaela; Osickova, Adriana; Filipi, Katerina; Jurnecka, David; Khaliq, Humaira; Espinosa-Vinals, Carlos; Pompach, Petr; Masin, Jiri; Osicka, Radim (International journal of biological macromolecules, 2024)
The RtxA cytotoxin, a member of the RTX (Repeats in ToXin) family of pore-forming toxins, is the primary virulence factor of the paediatric facultative pathogen Kingella kingae. Although structure-function studies of RTX toxins have defined their characteristic domains and features, the exact membrane topology of RTX toxins remains unknown. Here, we used labelling of cell-bound RtxA with a membrane-impermeable, lysine-reactive reagent and subsequent detection of the labelled lysine residues by mass spectrometry, which revealed that most of the membrane-bound toxin is localised extracellularly. A trypsin protection assay with cell-bound RtxA demonstrated that five of seven transmembrane α-helices, predicted by various algorithms within the N-terminal half of the molecule, are irreversibly embedded in the membrane. Structure-function analysis showed that these α-helices, four of which are arranged as two pairs of back-to-back helices, are essential for the formation of an ion-conducting membrane pore. In contrast, the C-terminal half of RtxA is required for the interaction with the cell surface and for the irreversible insertion of the toxin into the membrane via acyl chains covalently linked to the molecule. These findings advance our understanding of the structure-function relationships of RtxA and enable us to propose a membrane topology model of the toxin.
Keywords: Structure-Activity Relationship; molekulární modely; vztahy mezi strukturou a aktivitou; Bacterial Toxins; Models, Molecular; Cell Membrane; RtxA; buněčná membrána; Structure-function; Membrane topology; konformace proteinů, alfa-helix; Protein Conformation, alpha-Helical; Kingella kingae; bakteriální toxiny